2015
DOI: 10.1021/acs.jpcb.5b02715
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bridged Proton Structure in HTFSI Acid Ionic Liquid Solutions

Abstract: Acidic ionic liquid (AIL) solutions were prepared by dissolving bis(trifluoromethanesulfonyl)imide (HTFSI) acid in the ionic liquid (IL) 1-butyl-3-methylpyrrolidinium bis(trifloromethanesulfonyl)imide (PyrrTFSI). The HTFSI/PyrrTFSI solutions were investigated by conductivity measurements, optical spectroscopy, and DFT calculations in order to understand the ionization/solvation mechanism of HTFSI in the solutions. The HTFSI/PyrrTFSI solution conductivities first increased at lower concentrations and then decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…3b). 30,31 The ν 1 and ν 3 stretching modes give a very broad band centered at 2920 cm -1 , which overlaps the sharper maximum at 2880 cm 45 Thirdly, DSC measurements revealed a single endothermic peak and a corresponding exothermic peak (see Fig. 4).…”
Section: Synthesis Of [H 3 Omentioning
confidence: 83%
“…3b). 30,31 The ν 1 and ν 3 stretching modes give a very broad band centered at 2920 cm -1 , which overlaps the sharper maximum at 2880 cm 45 Thirdly, DSC measurements revealed a single endothermic peak and a corresponding exothermic peak (see Fig. 4).…”
Section: Synthesis Of [H 3 Omentioning
confidence: 83%
“…Similarly, the worst performer (PEDOT:PMATFSILi80) is the one that swells the least. The swelling behavior of these polymers is mainly due to H‐bonds and electrostatic interactions inherent to the >N ‐ H + moieties coming from TFSI side groups . It should be noted that while the response time should depend on the ionic conductivity of the channel, and hence correlate with the degree of swelling of the conducting polymer film, such correlation is not observed here (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…HTFSI solutions in PyrrTFSI show very interesting conductivity change behaviors. The solution conductivity increases at lower concentrations and decrease at higher concentrations; a maximum conductivity value can be observed at ~1 M HTFSI [6]. The HTFSI partially ionizes in the solution and a N-H-N "bridged" structure may be formed in the solution, in which a proton is solvated by two TFSI anions.…”
Section: Msa In 04 M and 20 M Htfsi/pyrrtfsimentioning
confidence: 97%
“…In our previous reports, we investigated the properties of a series of acid solutions in ILs such as 3-butyl-1-methylimidazolium tetrafluoroborate (BMIBF 4 ) [3], 3-butyl-1-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMITFSI) [4,5], N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PyrrTFSI) [6], and 3-ethyl-1-methylimidazolium acetate (EMIOAc) [7]. It has been concluded that the AIL properties strongly depend on the structures of ILs or acids.…”
Section: Introductionmentioning
confidence: 99%